Morfologia de las especies de mycosphaerella asociadas a manchas de las hojas en musa spp. - Perez Vicente, L.
(Es, En)
Ilus., 20 ref.
Keywords: MYCOSPHAERELLA; ENFERMEDADES FUNGOSAS; HOJAS; MUSACEAE; SINTOMAS; CUBA; SIGATOKA AMARILLA; SIGATOKA NEGRA; MANCHAS DE LAS HOJAS